2011
DOI: 10.1051/0004-6361/201015884
|View full text |Cite
|
Sign up to set email alerts
|

Reynolds stress and heat flux in spherical shell convection

Abstract: Context. Turbulent fluxes of angular momentum and enthalpy or heat due to rotationally affected convection play a key role in determining differential rotation of stars. Their dependence on latitude and depth has been determined in the past from convection simulations in Cartesian or spherical simulations. Here we perform a systematic comparison between the two geometries as a function of the rotation rate. Aims. Here we want to extend the earlier studies by using spherical wedges to obtain turbulent angular m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
122
2
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(155 citation statements)
references
References 55 publications
30
122
2
1
Order By: Relevance
“…As the rotation rate of the system decreases, the high-latitude cell extends to lower latitudes, ultimately supplanting the counter cell in the equatorial regions for rotation rates lower than  Ω . The shift from multi-cellular MC profiles in the solar regime to single-celled profiles in the antisolar regime has also been noted by other authors (Guerrero et al 2013a;Gastine et al 2014;Käpylä et al 2014). …”
Section: Identification Of Mean-flow Regimessupporting
confidence: 75%
See 1 more Smart Citation
“…As the rotation rate of the system decreases, the high-latitude cell extends to lower latitudes, ultimately supplanting the counter cell in the equatorial regions for rotation rates lower than  Ω . The shift from multi-cellular MC profiles in the solar regime to single-celled profiles in the antisolar regime has also been noted by other authors (Guerrero et al 2013a;Gastine et al 2014;Käpylä et al 2014). …”
Section: Identification Of Mean-flow Regimessupporting
confidence: 75%
“…Equatorial and polar rotation rates were calculated by averaging zonal velocity in both longitude and depth, and then over a latitude range of 0°N-20°N latitude and 70°N-90°N, respectively. Anti-solar cases tend to arise when Ro is greater than about 0.163. case B0.5 is just straddling the transition between the solar-like and anti-solar regimes of DR. Gastine et al (2014) and Käpylä et al (2014) have recently shown that the behavior of the DR near the solar/anti-solar transition can depend on the history of the simulation, representing a type of hysteresis. For a given transitional Ro, the simulation may exhibit either solar or anti-solar DR.…”
Section: A Transitional Regimementioning
confidence: 99%
“…We have shown earlier by means of quasilinear turbulence theory that the function V is negative and exists mainly in the supergranulation layer, while H is positive and exists mainly in the bulk of the convection zone. Numerical simulations provide very similar results (Chan 2001;Käpylä et al 2011; for more details see Rüdiger et al 2013). We also know that the positive quantity H in (5) and (6) both contribute to the equatorial acceleration so that it is not trivial to find the sign of (4) as a function of depth.…”
Section: Introductionmentioning
confidence: 54%
“…Inserting (2) and the second term in (1) into (3), one finds Ω dependent on r but independent of θ. For positive radial shear in the rotation law, on the other hand, a meridional flow toward the equator is induced at the surface, which accelerates the equator by transporting angular momentum (Kippenhahn 1963). Such a meridional flow, however, has not been observed so far.…”
Section: Introductionmentioning
confidence: 97%
“…Authors of these studies have been able to lower the diffusivity level low enough to yield more time dependent dynamo solutions possessing both cyclic behavior, regular butterfly diagram and torsional oscillation-like behavior (Käpylä et al 2011(Käpylä et al , 2012Dubé and Charbonneau 2013;Beaudoin et al 2013;Augustson et al 2013). Some have even obtained for the first time buoyant magnetic wreaths (Nelson et al 2011(Nelson et al , 2013.…”
Section: Nonlinear Dynamo Effect Magnetic Activity and Cyclesmentioning
confidence: 99%